Faktor-Faktor yang Berhubungan dengan Pelaksanaan Dokumentasi Asuhan Keperawatan Berbasis Komputer - Sianturi, Sondang Ratnauli; Afriana, Denny; Lina, Rosa Nora (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
Documentation is an important part of nursing care as it is one of many essential functions of a nurse that known to affect nursing care service quality given to the patients. The following research is aimed to know factors that are related to computer-based documentation of nursing care. This research is a quantitative research with descriptive correlation design and cross-sectional approach. 121 nurses as respondents were obtained with purposive technique sampling. Univariate analysis result shows that the majority of respondents’ age with 58 respondents (47.9%), the majority of level of education is Diploma III in nursing with 85 respondents (70.2%) and profession studies in nursing with 36 respondents (29.8%). Respondents who received training previously and received supervision were recorded with 95 respondents (78.5%) and 97 respondents (80.2%) respectively. Respondents with good motivation on the subject matters were recorded with 59 respondents (48.7%). The results of the Chi Square analysis test showed that there was a relationship between training (p-value ,008), supervision (p-value ,007) and motivation (p-value ,002) and there was no relationship between the age of the respondents (p-value ,983), and the level of education of the respondents (p-value ,792) with the implementation of computer-based nursing care documentation. For this reason, training, periodic supervision and motivating nurses in carrying out computer-based nursing care documentation are needed.